Assessing the internal and external factors influencing employee absenteeism : a case of the Ministry of Works and Transport in Windhoek and Swakopmund, Namibia - Simushi, Richard Lutombi (Stellenbosch : Stellenbosch University, 2020)
Thesis (MPA)--Stellenbosch University, 2020.